PENGARUH NILAI PELANGGAN DAN KEPUASAN TERHADAP LOYALITAS ANGGOTA CREDIT UNION KELING KUMANG NANGA PINOH KABUPATEN MELAWI - Mochammad Faisal Fadli (Jurnal Ekonomi Integra, 2019)
This study aims to determine the effect of customer value and satisfaction on the loyalty of members of the Credit Union Keling Kumang Nanga Pinoh Melawi Regency. The number of respondents was 100 respondents. The instrument used for data collection was in the form of a Likert scale questionnaire. This type of research is causal research design is research that is useful for analyzing the relationships between one variable with another variable or how a variable affects other variables. Based on data processing using regression analysis, it is evident that customer value and satisfaction have a significant effect on the loyalty of respondents as members of CU. Keling Kumang in Nanga Pinoh, Melawi Regency. The magnitude of the effect of customer value and satisfaction variables on the rise and fall of values or variations in the loyalty variable is 30.60% while 69.40% is influenced by other variables besides the variables in this study